Natural Language Processing and Information Systems 15th International Conference on Applications of Natural Language to Information Systems, NLDB 2010, Cardiff, UK, June 23-25, 2010. Proceedings - Hopfe, Christina J.; Rezgui, Yacine.; Mťais, Elisabeth.; Preece, Alun.; Li, Haijiang. (Lecture Notes in Computer Science, 2010)
This book constitutes the proceedings of the 15th International Conference on Applications of Natural Language to Informations Systems, held in Cardiff, UK, in June 2010.